ÁDEBIY ERTEK JANRÍ HAQQÍNDA - Sultanova, J.B. (SCIENCE and SOCIETY, 2025)
The article discusses the problem of formulating the genre of a literary fairy tale. The correlation of the folklore (folk) tale with the modern literary one is analyzed. Based on the conducted research, the author identifies some definitions of the term "literary fairy tale", formulates a connection with a folk tale and differences from it.
Keywords: folk folklore; fairy tale; author; genre; literary tale